Chinchorro culture: An analysis from the learning perspective - Liliana Pedraja-Rejas; Emilio Rodríguez-Ponce; Camila Muñoz-Fritis; Miguel-Ángel Garrido-Tamayo; Javier Vélez; David Laroze (Social Sciences and Humanities Open)
This study aims to identify trends in scientific production in the Chinchorro culture from the view of learning. With this aim, a bibliometric and content analysis of the journal articles indexed to the Web of Science database and Scopus on this topic (through September 2023) was carried out. Bibliometrix and VOSviewer were used for data processing. The results revealed that the University of Tarapacá (Chile) is at the center of scientific production in the field, standing out for its productivity and influence, which has allowed the consolidation of a body of researchers recognized for their impact in the area. Regarding the topics addressed, three main areas of study were found: 1) pathologies and toxicity, 2) life, society and cultural interactions, and 3) funerary traditions and mummification. The inclusion of the settlements and the artificial mummification process of the Chinchorro Culture on the World Heritage List by UNESCO has been the impetus behind this study. The authors are confident that this important achievement will foster an increase in scientific production, both nationally and internationally, in the coming years.